Corn Silk (Stigma maydis L.) as a Medicinal and Aromatic Plant: Phytochemical Diversity, Bioactivity, and Functional Applications: A Systematic Literature Review - Wahyu Purwanjani; Rosdiana Syakur (Postgraduate, University of Mataram, 2026)
Corn silk (Stigma maydis L.), the stigmatic tissue of maize (Zea mays L.), has long been used in traditional medicine for urinary and metabolic disorders. Although previous reviews have described its medicinal properties, current evidence remains fragmented across phytochemical, pharmacological, and functional studies, highlighting the need for a comprehensive systematic synthesis. This systematic literature review aimed to synthesize and critically evaluate evidence on the phytochemical composition, pharmacological activities, and functional applications of corn silk while identifying current research gaps and future research directions. A PRISMA-guided systematic search was conducted using Scopus, Google Scholar, and selected publisher databases for English-language studies published up to December 2024. Eligible peer-reviewed articles investigating corn silk phytochemistry, bioactivities, toxicity, or functional applications were screened according to predefined inclusion and exclusion criteria. Nineteen studies met the eligibility criteria and were included in the qualitative synthesis. Corn silk is rich in flavonoids, phenolic acids, polysaccharides, and bioactive peptides, exhibiting antioxidant, anti-inflammatory, antidiabetic, antihypertensive, and organ-protective activities. Emerging applications include functional foods, cosmeceuticals, and eco-friendly bioproducts. Corn silk demonstrates considerable therapeutic potential; however, further standardized studies and clinical validation are needed to support its evidence-based application.